Popular Protestantism in Ulster in the Post-Rebellion Period, c1790-1810 - Hill, Myrtle (Studies in church history, 1989)
Popular Protestantism in Ulster in the late eighteenth and early nineteenth centuries, characterized by variety and liveliness, was directly related to events of more immediate national significance. While remaining a mere undercurrent in Irish affairs, Ulster evangelicalism in this important transitional period—shaped and moulded by the rebellion, the Act of Union, and the rise of a more articulate and assertive Catholicism—laid the foundations of a scripture-based, politically conservative Protestantism, which continues to influence the province’s social and political development.